An overview of the genetic diversity of Echinococcus granulosus sensu lato in Turkey - Serra Örsten; Gülay Maçin; Sümeyye Başer; Salih Maçin (Journal of Contemporary Medicine, 2022)
Echinococcus granulosus is a parasite that lives as a host in animals and humans, causes great economic damage and poses a serious threat to health. Morphological differences and intermediate host preference are used to distinguish the species of this parasite. Ten genotypes and lion strains of Echinococcus granulosus have been identified in molecular studies to date. It contributes to the fact that the effects of cystic echinococcosis detected in humans and the disease process caused by different genotypes can be handled differently. In genetic diversity analysis, species were classified as Echinococcus granulosus sensu stricto, Echinococcus equinus, Echinococcus ortleppi, Echinococcus canadensis and Echinococcus felidis genotypes. Echinococcus granulosus sensu stricto is the most common cause of human cystic echinococcosis worldwide and in Turkey. In this review, the distribution and epidemiology of Echinococcus granulosus genotypes detected in humans and animals in Turkey are discussed.